Replenishment of muscle glycogen in the recovery of the athlete - Mata-Ordoñez, F.; Grimaldi-Puyana, M.; Sánchez-Oliver, A. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Nutritional interventions play a fundamental role during the post-exercise recovery phase. One of the main goals of recovery is restoring muscle glycogen stores. This becomes more important when athletes are subjected to intense training or competition with short recovery periods be-tween bouts. Furthermore, manipulating muscle glycogen availability can improve molecular adaptations to training. The objective of this review is thus to present the basic physiological aspects of this phenomenon, and to discuss carbohydrate consumption, timing, type, and amount, as well as its interaction with different nutrients, in order to maximize or play with the restoration of muscle glycogen depending on the needs and/or the strategies proposed. Glyco-gen should no longer be seen as a simple form of energy storage, but as a molecule that can trigger numerous cellular processes important for athletic performance.